Symphony No. 3 in E-flat Major, Op. 55 Eroica - Beethoven, Ludwig van. 1770-1827 (Colección Dover Miniature Scores, 1997)
Completed in 1804, the "Eroica" Symphony marked a profound turning point in Beethoven's personal and professional life. Confronted by severe and progressive hearing loss, the composer drew upon immense inner reserves to create one of his most dynamic and expressive works. Original in structure and form, the epochal "Eroica" signaled the composer's break with classical precedents and initiated an irrevocable change in the course of symphonic music. The design and craftsmanship of the work astonished and delighted audiences, and brought its already distinguished creator critical acclaim as a "complete, consummate artist." Long a staple of the orchestral repertoire, the Symphony No. 3 is published here in full score, with bar-numbered movements. This convenient, affordable volume is the edition of choice for study in the classroom, at home, or in the concert hall. Unabridged Dover (1997) republication of the H. Litolff edition.